Fractals Study and Its Application - Setyawan Widyarto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
The overall of this paper is a review of fractal in many areas of application. The review exposes fractal deﬁnition, analysis, and its application. Most applications discussed are based on analysis from geometric and image processing studies. Patterns of some fractals will be discussed. Some simulation results are supplied to illustrate the discussion. Simulation resulted are from various software and tools. Some principles of fractals with informative patterns have been simulated. Whereas the simulations could support some recommendations for prospective purposes and applications. The prospective application may help in predictive pattern of many ﬁelds. The predictive pattern will lead to pattern control and pattern disruptions.